Exploring the Gastrointestinal Microbiome of Eurasian Griffon Vultures (Gyps fulvus) Under Rehabilitation in Portugal and Their Potential Role as Reservoirs of Human and Animal Pathogens - Mariana Limede Nascimento; Isa Serrano; Eva Cunha; Filipa Lopes; Pedro Pascoal; Marcelo Pereira; Mónica Nunes; Luís Tavares; Ricardo Dias; Manuela Oliveira (Veterinary Sciences)
The Eurasian griffon vulture (Gyps fulvus), a widely distributed scavenger, plays a crucial role in ecosystem health by consuming decomposing carcasses. Scavengers have adapted to avoid disease from the rotting carrion they feed on, probably through a specialized gut microbiome. This study aimed to characterize the gut microbiome of G. fulvus (n = 8) present in two rehabilitation centers in mainland Portugal and evaluate their potential as reservoirs of pathogens. Samples were studied through high-throughput 16S rDNA amplicon sequencing of the hypervariable V3-V4 regions and further analyzed using the Qiime2 bioinformatics platform. Our results showed that factors such as sex, location, and time of sampling did not significantly affect the gut microbiome of the griffon vulture. Its composition was highly similar to that of phylogenetically closed animals. However, several potential human and veterinary pathogens were identified. In conclusion, the gut microbiome of Gyps fulvus in rehabilitation centers is not significantly altered by stress associated with captivity. Its composition is similar to that of other vultures and scavengers due to their identic diet and needs, suggesting a well-conserved functional gut microbiome, which seems to be influenced by season. The potential risks posed by the identified pathogens to humans and other animals should be further investigated.